ANALISIS POLA MANAJEMEN BAHAN BAKAR TERAS REAKTOR RISET TIPE MTR - Suparlina, Lily; Surbakti, Tukiran (Jurnal Teknologi Reaktor Nuklir Tri Dasa Mega, 2015)
Research reactor core design needs neutronics parameter calculation use computer codes. Research reactor MTR type is very interested because can be usd as research and also a radioisotope production. The research reactor in Indonesia right now is already 25 years old. Therefore, it is needed to design a new research reactor as a compact core. Recent research reactor core is not enough to meet criteria acceptance in the UCD which already determined namely thernmal neutron flux in the core is 1.0x1015 n/cm2s. so that it is necessary to be redesign the alternative core design. The new research reactor design is a MTR type with 5x5 configuration core, uses U9Mo-Al fuel, 70 cm of hight and uses two certainly fuel management pattern. The aim of this research is to achieve neutron flux in the core to meet the criteria acceptance in the UCD. Calculation is done by using WIMSD-B, Batan-FUEL and Batan-3DIFF codes. The neutronic parameters to be achieved by this calculation are the power level of 50 MW thermal and core cycle of 20 days. The neutronis parameter calculation is done for new U-9Mo-Al fuel with variation of densities. The result of calculation showed that the fresh core with 5x5 configuration, 360 gram, 390 gram and 450 gram of fuel loadings have meet safety margin and acceptance criteria in the UCD at the thermal neutron flux is more then 1.0x1015 n/cm2s. But for equilibrium core is only the 450 gram of loading meet the acceptance criteria.